Strengthening Character Education of Madrasah Students Based on Boarding School - Asep Azis Nasser; Trisnamansyah, Sutaryat; Achmad Mudrikah; Iriantara, Yosal (International Journal of Educational Research & Social Sciences, 2022)
The title of this research is Strengthening Character Education in Boarding School- Based Madrasah Students (Case Study at MAN Insan Cendekia Serpong) in 2021. This research is based on the phenomenon of the existence of boarding school- based educational institutions so it is necessary to find a model that becomes a reference for its implementation by focusing on strengthening efforts for character education for madrasah students. The purpose of this study was to obtain an overview of efforts to strengthen character education for Islamic boarding school- based students of Madrasah Aliyah Negeri Serpong. Efforts to strengthen character education in question include three main things, namely: basic concepts of learning good character knowledge, forms of good character building, and habituation of good character actions. The research approach used is a qualitative approach with a case study method. This approach and method is considered appropriate for the fulfillment of efforts to obtain a clear picture of how efforts are made to strengthen character education at MAN Insan Cendekia Serpong. The two main areas are the cultivation of Science and Technology and the cultivation of Faith and Piety. In the results of the study, it was found that MAN Insan Cendekia Serpong was able to integrate the academic curriculum in the classroom with a unified boarding curriculum into a unified whole in the education process for students while in the boarding school environment. The integration of the academic curriculum and the dormitory indicates seriousness in implementing strengthening student character education. The practice that has been running at MAN Insan Cendekia Serpong is very much in line with the main theory of this research by referring to Lickona's opinion which states that character education must begin with knowing the good, feeling the good, and doing the good. Several factors that support the strengthening of character education at MAN Insan Cendekia Serpong are the basic concepts in learning that emphasize character knowledge both fundamentally and intensively when studying in class or while in the dormitory. The fostering of good character feelings is also continuously developed by the role of the guardian of the dormitory, the teacher of dormitory development, and the foster teacher. The process of habituation of good character actions is strengthened by the schedule of activities and spontaneous actions of students who are driven by the knowledge and feelings of good character that are very well embedded. From the many facts obtained, of course there are still some notes that must be improved as an effort to make improvements to be better and more perfect